PEM fuel cells : theory, performance and applications - Buchanan, Felicia (Energy science, engineering and technology series., 2014)
Proton Exchange Membrane (PEM) fuel cells are still undergoing intense development, and the combination of new and optimized materials, improved product development, novel architectures, more efficient transport processes, and design optimization and integration are expected to lead to major gains in performance, efficiency, durability, reliability, manufacturability and cost-effectiveness. The potential of fuel cells as an energy source to replace fossil fuels in a wide range of applications, has now become a reality that is environmentally friendly and helps support the sustainable developme.